Aerobic Degradation of 1,1,1-Trichloroethane by Mycobacterium spp. Isolated from Soil - Yagi, Osami (American Society for Microbiology, 1999)
Two strains of 1,1,1-trichloroethane (TCA)-degrading bacteria, TA5 and TA27, were isolated from soil and identified as Mycobacterium spp. Strains TA5 and TA27 could degrade 25 and 75 mg · liter of TCA(−1) cometabolically in the presence of ethane as a carbon source, respectively. The compound 2,2,2-trichloroethanol was produced as a metabolite of the degradation process.